In Vitro Evaluation of Microbial Leakage in Different Root Canal Obturation Techniques - Alakesh Singha; Keshav K. Manglam; Nishita Grandhi; Lipsa Bhuyan; Subasish Behera; Soumyaranjan Nanda; Mahesh Ghadage; Bhumika J. Patel (Journal of Pharmacy and Bioallied Sciences)
Background: Because it allows germs to enter the root canal system, microbial leakage is a primary cause of endodontic failure. The goal of various root canal obturation procedures is to create a hermetic seal that stops microbes from penetrating. Materials and Procedures: The ProTaper Universal system was used to prepare 60 removed human mandibular premolars for this in vitro investigation. Based on the obturation method, the teeth were randomly assigned to three groups (n = 20): Group 1: lateral compaction of gutta-percha, Group 2: thermoplasticized gutta-percha, and Group 3: single-cone obturation. To measure microbial leakage, Enterococcus faecalis was introduced into each sample. The samples were cultured for 30 days to track the bacteria’s ability to pass through the obturated canals. Turbidity in the culture media was used to assess microbial leakage, and microbial culture tests were used to corroborate the findings. Results: The findings demonstrated that 12 samples (60%) in Group 1, eight samples (40%) in Group 2, and 15 samples (75%) in Group 3 had microbial leakage. The single-cone approach showed the largest microbiological leakage, whereas the thermoplasticized gutta-percha group showed the least amount, followed by lateral compaction. According to statistical analysis, there was a significant difference in leakage across the groups (P < 0.05). Conclusion: In contrast to lateral compaction and the single-cone method, thermoplasticized gutta-percha offered the greatest barrier against microbial leakage. This implies that endodontic failure brought on by bacterial contamination may be avoided more successfully using thermoplasticized procedures.